Paradigma Pembangunan Berkelanjutan Sosial, Ekonomi dan Ekologi: Studi Keberlanjutan Ecovillage Das Citarum - A Hadian Pratama Hamzah; Nurhasanah; Sohifah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to identify the elements influencing the sustainability of ecovillage development in 49 villages located in the Citarum Watershed. The method used was qualitative, through field observation, interviews, and data and information collection. Prospective analysis results show that in the Ecological Dimension, there are four main influencing elements: (1) utilization of agricultural waste; (2) disposal of agricultural waste; (3) fertilization techniques; and (4) conservation activities. In the Economic Dimension, three main elements were identified: (1) community support in selling recycled products; (2) community support in creating employment; and (3) development of post-harvest household production. In the Social Dimension, four main elements were found: (1) support from local government; (2) joint commitment of all stakeholders; (3) institutions emphasizing support for environmental programs; and (4) community involvement. In conclusion, the sustainability of ecovillage development in the Citarum Watershed is influenced by four key elements: support from local government, joint agreement among all stakeholders, institutions emphasizing support for environmental programs, and community involvement in environmental activities, with three strategic plans: pessimistic, moderate, and optimistic. Keywords: Citarum Hulu, Ecovillage, Environment, Sustainability, Watershed